Measuring potential tax non-compliance in the Indonesian tax system: A meta-analysis - Diyah Probowulan; Achmad Syahfrudin Zulkarnnaeni (The Indonesian Accounting Review, 2022)
This study aims to assess, firstly, the potential for taxpayers' non-compliance from previous studies that are dominant between tax avoidance and tax evasion due to active resistance in the taxation system in Indonesia. Secondly, it also tries to assess and parse the ability of the taxation system in Indonesia to prevent taxpayers from being disobedient. This study used a meta-analysis for the data analysis with the moderating variable regression equation of the taxation system. The results show that high tax sanctions and stable financial conditions can minimize the potential for tax non-compliance, while the quality of tax services, compliance costs, and tax socialization from 12 study samples have not been able to be used as factors to reduce the potential for tax non-compliance. This study also identifies the tendency of tax non-compliance behavior to be dominated by tax evasion. The originality of this study lies in using the meta-analysis method and using a dummy on the dependent variable to see the potential for non-compliance between tax avoidance and tax evasion. The implications of this study provide important insights for policymakers and government leaders in designing fiscal policies to minimize the social phenomena of tax non-compliance and build a tax compliance mindset and also redesign a tax system that is more credible, easy to understand, and prevents loopholes a system that the taxpayer can utilize.